2018
DOI: 10.29007/584l
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Trajectory Detection using Recurrent Neural Network

Abstract: Anomalous trajectory detection which plays an important role in taxi fraud detection and trajectory data preprocessing is a crucial task in trajectory mining fields. Traditional anomalous trajectory detection methods which utilize density and isolation approaches mainly focus on the differences of a new trajectory and the historical trajectory dataset. Although these methods can capture the particular characteristics of trajectories, they still suffer from the following two disadvantages. (1) These methods can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The latter group uses historical data to learn the implicit detection rules. Since no representative groundtruth data are available for maritime anomaly detection, learningbased anomaly detection schemes cannot apply supervised methods like in [5]- [7]. Unsupervised learning methods are then preferred [9]- [11], [16], [22], [23], [27].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter group uses historical data to learn the implicit detection rules. Since no representative groundtruth data are available for maritime anomaly detection, learningbased anomaly detection schemes cannot apply supervised methods like in [5]- [7]. Unsupervised learning methods are then preferred [9]- [11], [16], [22], [23], [27].…”
Section: Related Workmentioning
confidence: 99%
“…For these reasons, anomaly detection methods used in other domains such as network traffic analysis or cybersecurity [3], [4] do not apply. We may also emphasise there are no representative groundtruth datasets for this task, hence, supervised learning strategies for anomaly detection as in [5]- [7] do not apply either.…”
Section: Introductionmentioning
confidence: 99%
“…Next, a bag-of-roads method, similar to bag-of-words, generates vectors of the buses and vectors of the predefined routes, which are used by a KNN model to perform bus route classification. Song et al [31] introduce a binary classifier to detect spatial anomalies in taxi trajectories. For that, they first map trajectories into a regular grid map.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Goh et al [9] proposed a novel rough neural network-based model named radial basis function network with dynamic decay adjustment (RBFNDDA) to learn information directly from a data set and group it in terms of prototypes, and then, a neighbourhood rough set-based procedure was applied to detect prototype outliers. Song et al [10] found the difficulty in learning the normal patterns and the problem of data sparsity and proposed anomalous trajectory detection using recurrent neural network (ATD-RNN) which learned the trajectory embedding to characterized the trajectory. Then, Cheng et al [11] used coordinate sequence and spatio-temporal sequence and proposed spatio-temporal recurrent neural network (ST-RNN) and added attention mechanism.…”
Section: A Lstm Predictionmentioning
confidence: 99%
“…In practical application, we can find that the length of multiple trajectory data in the trajectory data set may not be the same, and there may be some problems such as missing data or different receiver working mechanism, resulting in data sparsity. When [10] researched on the same starting point trajectory modelling for trajectories with given departure and destination, they utilized some padding operations to align trajectories by using relevant trajectories. But this method needs enough prior knowledge of geography, increased the difficulty of data acquisition and data processing workload.…”
Section: A Normal Trajectory Modellingmentioning
confidence: 99%